Car dependency phenomenon in Pulau Pinang - Caisarina, Irin; Mat, Hassim (2008)
Malaysia has been through the phenomenal economic growth in the past two decades. The significant changing is started from structural transformation, economic growth to the increasing cities, at the same time is followed by the escalating of car traffic, especially the growing of car ownership and its usage. The main problem that comes from car ownership is congestion where Penang Island is on the third place after Kuala Lumpur Federal Territory and Johor Bahru for car ownership. This elevated rate of the car ownership can drive us to the phenomenon of car dependency, which needs serious attention from the authorities. Therefore, government policy should be more adequate to handle the car dependency; such as by strengthening the governmental policies, traffic regulations and public transportations. Besides trying to analyze the problems that have been faced by Penang Island, which are: factors that caused car dependency, the effect of car dependency and the using of public transport, this paper also try to give alternatives and necessary actions that can be considered to reduce the car dependency in Penang Island.